NILAI PENDIDIKAN KARAKTER PADA TOKOH DALAM NOVEL CINTA SANG SUFI KARYA ALI ACHMAD BAKTSIR - Dwi Wardatul Khoir (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2018)
The Value of Character Education is a value of life to be developed in one's personality. This value is basic human character which constructed from religion, Pancasila, cultural value, and national education goals. In this research, Thescope of value of character education covered eighteen elements namely; religious, honest, tolerance, discipline, hard work, creative, independent, democracy, curiosity, national spirit, love of the motherland, respect for achievement, friendship and communication, peace-loving, fond of reading, care about the environment, care about social and responsibility. Character in a literary work is a crucial element since without their existence the ideas and messages will be hardly conveyed.  Each character has a different role in delivering their messages and ideas. There are three types of character in this novel; protagonist, antagonist, and tritagonist.This study was conducted by using qualitative method. The data used were narratives, descriptions, dialogues, and actions taken form the characters. Meanwhile, the data collection techniques were set out by observation, literature study, read and note, and description. The data source was the novel Cinta Sang Sufi by Ali Achmad Baktsir, published by Idola Qta, Yogyakarta 2009 which consists of 281 pages. Data analysis techniques were conducted by doing some steps; reading data, selecting, coding, classifying, describing, analyzing and inferring.The results showed that the protagonist characters in the novel are Hakim, Salamah, Abdurrahman, and Ibnu Suhail. Meanwhile, the antagonist character named Umar, and the tritagonist character were Abul Wafa and Ummul Wafa. The value of character education contained in this novel is active in religious activities, the honest value is the main character never lied, tolerance with friends, discipline, work hard, work earnestly, independently, have a curiosity, friendly, and communicative.  .